(untitled) (Research, Society and Development, 2023)
The in vitro embryo production (PIV) is a biotechnique used, alternatively, to accelerate the production of genetically superior animals, with different stages: collection and in vitro maturation of oocytes, in vitro fertilization, in vitro culture from zygotes to the blastocyst stage. PIV, in conjunction with oocyte and embryo cryopreservation, may enable large-scale commercialization of embryos, transport of pathogen-free embryos, and easier and lower-cost germplasm commercial transactions. However, it is not effective due to several factors related to the evolution of the process. Studies aim to facilitate the use of oocytes for biological and commercial reasons and better cell utilization. A narrative review of the literature was carried out, through scientific articles, dissertations, theses and books published in the databases: Scopus, PubMed, Scielo and Google Scholar, with the aim of providing an overview of this biotechnique in goats with emphasis on the description emphasizing the main methodologies currently used for oocyte collection, IVM, IVF and IVC of embryos.